After 50 Years: Ongoing Renewal of Moral Theology - Kochuthara, Shaji (Asian Horizons, 2015)
Though Vatican II has not promulgated a separate document on moral theology, we find a tremendous development in moral theology since Vatican II. The groundwork for the renewal of moral theology was begun in the first half of the twentieth century by moral theologians like Dom Odon Lottin, Fritz Tillmann, Gérard Gillemann, Dietrich von Hildebrand, Herbert Doms, Bernard Häring, Josef Fuchs and so on. The Council gave a definitive direction to its further development. Optatum Totius, 16 gives Vatican II’s basic guidelines for the renewal of moral theology.